Myostatin Mutation Promotes Glycolysis by Increasing Phosphorylation of Phosphofructokinase via Activation of PDE5A-cGMP-PKG in Cattle Heart - Gu, Mingjuan; Zhou, Xinyu; Zhu, Lin; Gao, Yajie; Gao, Li; Bai, Chunling; Yang, Lei; Li, Guangpeng (Frontiers in Cell and Developmental Biology, 2022)
Myostatin (MSTN) is a primary negative regulator of skeletal muscle mass and causes multiple metabolic changes. However, whether MSTN mutation affects heart morphology and physiology remains unclear. Myostatin mutation (MT) had no effect on cattle cardiac muscle in histological examination, but in biochemical assays, glycolysis increased in cattle hearts with MT. Compared with wild-type cattle, there were no differences in mRNA and protein levels of rate-limiting enzymes, but phosphofructokinase (PFK) phosphorylation increased in cattle hearts with MT. Transcriptome analysis showed that phosphodiesterase-5A (PDE5A), a target for inhibiting cGMP-PKG signaling, was down-regulated. For the mechanism, chromatin immunoprecipitation qPCR showed that the SMAD2/SMAD3 complex in the canonical downstream pathway for MSTN combined with the promoter of PDE5A. The cGMP-PKG pathway was activated, and PKG increased phosphorylation of PFK in cattle hearts with MT. In addition, activation of PKG and the increase in PFK phosphorylation promoted glycolysis. Knockdown of PKG resulted in the opposite phenomena. The results indicated that MT potentiated PFK phosphorylation via the PDE5A-cGMP-PKG pathway and thereby promoted glycolysis in the heart.